2017
DOI: 10.1007/s11128-017-1626-7
|View full text |Cite
|
Sign up to set email alerts
|

SLOCC orbit of rank-deficient two-qubit states: quantum entanglement, quantum discord and EPR steering

Abstract: We study selected aspects of non-classical correlations of arbitrary states from the stochastic local operations and classical communication orbit of rankdeficient two-qubit states. In particular, we find explicitly entanglement of formation and quantum discord for these states. Moreover, we determine and analyze the Einstein-Podolsky-Rosen steering ellipsoids corresponding to these states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Examples include steered coherence, [42][43][44] discord, [38,[45][46][47] entanglement [38,41,48] and EPR steering. [49][50][51][52][53][54] Zhang et al [55] experimentally verified the QSE of two-qubit states and also demonstrated volume monogamy relations of the QSE. [56] Recently, Du et al [57] investigated quantum phase transitions in the XXZ model through a QSE.…”
Section: Introductionmentioning
confidence: 95%
“…Examples include steered coherence, [42][43][44] discord, [38,[45][46][47] entanglement [38,41,48] and EPR steering. [49][50][51][52][53][54] Zhang et al [55] experimentally verified the QSE of two-qubit states and also demonstrated volume monogamy relations of the QSE. [56] Recently, Du et al [57] investigated quantum phase transitions in the XXZ model through a QSE.…”
Section: Introductionmentioning
confidence: 95%
“…In the case of two-partite, finite dimensional system being in the pure state, the Schmidt decomposition of the corresponding pure state gives essentially all relevant information on the corresponding quantum correlations. From the quantitative point of view and from qualitative ((S)LOCC type, semi-order relations [2,3,4,20,21] point of view as well. The case of many-partite systems, and also the case of mixed (even for two-partite systems) states is much less recognised despite to many efforts [2,3,4,5,22].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the necessary and sufficient conditions for an ellipsoid to represent a two-qubit state were proposed by Milne et al [22]. Many properties of two-qubit system can be captured by QSEs, such as entanglement [21][22][23], discord [21,24,25] and EPR steering [26][27][28][29][30][31]. Recently, Hu et al have explored the effect of a local trace-preserving single-qubit channel on a two-qubit state in the frame of QSEs and found that the quantum discord of a two-qubit state can be increased by local operations in QSE pictures [32].…”
Section: Introductionmentioning
confidence: 99%